Entanglement and quantum discord in the cavity QED models - Hui-hui Miao; Wanshun Li (Heliyon)
We investigate the quantum correlation between light and matter in bipartite quantum systems, drawing on the Jaynes–Cummings model and the Tavis–Cummings model, which are well-established in cavity quantum electrodynamics. Through the resolution of the quantum master equation, we can derive the dissipative dynamics in open systems. To assess the extent of quantum correlation, several measures are introduced: von Neumann entropy, concurrence and quantum discord. The effects of initial entanglement and dissipation intensity on quantum discord are carefully examined. Furthermore, we examined the dynamics of quantum discord within the OH+ model.